Traditional knowledge and women’s postpartum care: the use of medicinal plants by women in the South-Central and Campos Gerais region, PR, Brazil (Terr@ Plural, 2022)
The goal of this study is to understand the use and material and symbolic appropriation of medicinal plants by women in the South-Central region of Paraná and Campos Gerais for postpartum care. To this end, 213 mothers who gave birth during the years 2006 to 2021 revealed that most of them experienced specific postpartum care provided by a relative, regardless of education, correlated to certain herbs and recipes from the regional biocultural heritage. The knowledge about postpartum care remains active, territorialized in the mind and body as a social strategy of resistance to the domination of knowledge. The historical and geographical approach to this cultural practice highlights the phenomenon of the re-signification of traditional knowledge about the care of the body and of life by women of the region in contexts of multiple modernities.
Keywords: parturients; postpartum care; traditional knowledge